The central-peripheral coupling effect of ocular acupuncture kinesitherapy in post-stroke dyskinesia: A functional neuroimaging and neurotic electrophysiology study protocol - Zhang, Di; Wang, Yongshen; Li, Hongpeng; Ma, Jiang; Sun, Jianfeng; Wu, Zhipeng; Zhang, Guilong; Jin, Song (Frontiers in Neurology, 2022)
Background: Dyskinesia is a common manifestation after stroke. Motor functional rehabilitation after stroke is of great significance to the maintenance of national health. Ocular Acupuncture Kinesitherapy (OAKT) can repair nerve injuries, improve motor function, reduce rehabilitation time, and promote dyskinesia recovery after stroke. The mechanism, however, remains a mystery, necessitating urgent research. The M1-thalamus-spinal cord neural signaling pathway is linked to limb motor function. Bold-fMRI can represent the cerebral functional state, and TMS-MEP is of certain practical utility for assessing motor neural function and prognosis. Combining fMRI scanning with TMS-MEP detection is predicted to advance brain-spinal cord regulation and muscle response linkage control mechanism research, as well as completely investigate the central-peripheral coupling effect of Ocular Acupuncture Kinesitherapy on dyskinesia after stroke (PSD). Methods: This is a prospective functional neuroimaging and neurotic electrophysiological study with a case-control design between the PSD with the HC groups and a randomized controlled design within the 3 PSD groups (OAKT group, ocular acupuncture group, and kinesitherapy group). Using fMRI scans and TMS-MEP approach, we will assess the central-peripheral neural function alterations in PSD as well as the coupling effects of OAKT on PSD. We plan to enroll 90 participants at the Hospital of Chengdu University of Traditional Chinese Medicine from Aug 31, 2022, to Dec 31, 2023, including 45 PSD and 45 HC subjects. After enrollment and on the last day after 4-weeks of waiting (HC subjects) or intervention (PSD subjects), all eligible subjects will be evaluated using fMRI scanning, TMS-MEP detection, and the MMT and Fugl-Mayer scales assessment. The MMT and Fugl-Meyer scores will be recorded, and a Pearson correlation analysis will be performed to assess the correlation between clinical and imaging outcomes. Discussion: Findings of this study will help to explain the central-peripheral coupling effect of OAKT on PSD and to further provide the neural processing of acupuncture kinesitherapy covering the entire pathway from peripheral to central nervous system.